2019
DOI: 10.3390/molecules24162916
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Maintains Lipid Metabolism Homeostasis via One of the Mechanisms Associated with the Key Circadian Regulator Bmal1

Abstract: Resveratrol (RES) possesses anti-inflammatory and anti-oxidant activities, and it can prevent liver lipid metabolism disorders in obese and diabetic individuals. This study elucidated the mechanisms of brain and muscle Arnt-like protein-1 (Bmal1) in the protective effects of RES against liver lipid metabolism disorders. The results indicated that RES ameliorated free fatty acid (FFA)-induced (oleic acid (OA): palmitic acid (PA) = 2:1) glycolipid metabolic disorders in hepatocytes. Simultaneously, RES partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…Many antioxidant molecules, such as plant phenolics (including simple flavonoids, coumarins, stilbenes, hydrolyzable and condensed tannins, lignans, and lignins) are known to show a peculiar hormesis effect on cells, namely at low doses they show protective effects on lipid metabolism, whereas, at higher doses they induce cell toxicity [ 28 ]. Few studies reported that resveratrol inhibits cell viability in a dose- and time-dependent manner [ 29 ]. For these reasons we tested açai extract at low doses on different cell models.…”
Section: Discussionmentioning
confidence: 99%
“…Many antioxidant molecules, such as plant phenolics (including simple flavonoids, coumarins, stilbenes, hydrolyzable and condensed tannins, lignans, and lignins) are known to show a peculiar hormesis effect on cells, namely at low doses they show protective effects on lipid metabolism, whereas, at higher doses they induce cell toxicity [ 28 ]. Few studies reported that resveratrol inhibits cell viability in a dose- and time-dependent manner [ 29 ]. For these reasons we tested açai extract at low doses on different cell models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DHA from the algal oil was also shown to regulate the circadian rhythm of Phase shift in Clock and Bmal1. [110] blood lipids in mice via the action of rhythmic nuclear receptors and downstream pathways involved in cholesterol and bile acid synthesis, thereby improving blood lipid profiles. [71] Similarly for MUFAs, oleic acid was capable of restoring the rhythmicity of clock genes in stomach and jejunal explants obtained from individuals with morbid obesity.…”
Section: Fatsmentioning
confidence: 99%
“…Compounds such as Resveratrol, nobiletin, piceatannol, and ursolic acid have been shown to be capable of ameliorating high fat diet‐induced circadian desynchrony in hepatocyte cultures and animal studies, by reverting disruptions and phase‐shifting clock genes involved in lipid and glucose metabolism. [ 109–112 ] Similarly, capsaicin was also shown to alleviate impaired glucose uptake, circadian misalignment, and redox imbalance induced by insulin resistance in HepG2 cells. [ 113 ] The intake of melanoidins were also capable of restoring circadian rhythmicity of gut microflora profiles in mice (from a high fat diet‐induced dysbiosis), thereby increasing the abundance of SCFA producers and reducing the oscillations of inflammatory species.…”
Section: Dietary Components Intake Timing and Their Interaction With ...mentioning
confidence: 99%
“…Multiple studies have shown that the misalignment of circadian rhythms is associated with various metabolic disorders, such as obesity, cancer, inflammatory response, insulin resistance, and diabetes [ 5 , 7 , 8 , 9 , 10 ]. Many phytochemicals with metabolism-modulation effects have been proved to restore normal circadian rhythm in cell models and animal models, such as tea polyphenols, resveratrol, cichoric acid, and capsaicin [ 11 , 12 , 13 , 14 , 15 , 16 ]. Guo et al reported that cichoric acid could attenuate the lipid metabolism dysfunction by modulating the circadian gene Bmal1 expressions in hepatocytes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%